The Urgency of Religious Moderation in Preventing Radicalism in Indonesia - Arifinsyah Arifinsyah; Safria Andy; Agusman Damanik (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
This paper aims to contribute to the thought of realizing religious moderation to prevent radicalism. The problem is, what is meant by religious moderation and how to do the deradicalization of religious moderation based harmony in Indonesia. This research used a qualitative method with content analysis techniques (content analysis), which examines and analyzes a number of literature (Library Research) related to the subject matter. Religious moderation is very significant in deradicalizing, namely; 1). Provide awareness of human nature to do good, the necessity of living side by side in the midst of heterogeneity, without cultural, religious and national boundaries. 2). A moderate attitude promotes hospitality and compassion, upholds human dignity, and lives a life based on religion, morals and universal ethics. 3). Religious people are aware of being citizens and at the same time becoming part of world citizens, respecting other truths. 4). Religious moderation is the most appropriate content and practice to prevent radicalism and preserve harmony in Indonesian earth, which is knitted with Pancasila values. Mental attitude that is moderate, fair, and balanced is the key to managing diversity. 5). With religious moderation, it will be able to manage plural and multicultural societies in the midst of the development of information technology in Indonesia. 6). Religious moderation becomes significant not only for the creation of constructive relations between religions externally, but it is also important internally to create harmony between various streams within one religion.